Growth and yield of tomato (Lycopersicon esculentum) genotypes in wet season on Entisol of Orissa - Singh, D N; Tripathy, P (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy season of 1992 to study growth and yield of 4 cultivars ('Pusa Ruby', 'LE 79', 'ST 1' and 'Arka Alok') of tomato (Lycopersicon esculentum Mill. nom. cons.), The cultivars showed significant variation for vegetative growth, fruit characters and yield among themselves when planted at different dates, 'LE 79' tomato gave the highest fruit yield (12.20 tonnes/ha) and 'Arka Alok' produced significantly bigger (20.29 cm) and heaviest fruits (136.71 g). Planting on 20 June was found signiticantly favourable for plant height (68.43 cm), branches/plant (7.30), compound leaves/plant (44.23) and fruit yield (17.15 tonnes/ha) as well as its attributing characters like fruit weight (60.83 g), length (4.77 cm) and girth (16.18 cm). Significantly higher positive correlation was observed between fruit yield and plant height (0.671), branches/plant (0.643), compound leaves/plant (0.575) and fruit length (0.495), and between fruit girth and fruit weight (0.959) and fruit length (0.649).